ANALISIS POTENSI DAN EFEKTIFITAS PAJAK DAERAH ATAS RUMAH KOS DI KOTA KOTAMOBAGU - Londa, Sugaray Emmanuelle; Kalangi, Lintje; Pangerapan, Sonny (GOING CONCERN : JURNAL RISET AKUNTANSI, 2017)
Increased Local Revenue is highly determined by its components, such as local taxes, and local taxes are also determined by the components of the tax itself. The boarding house is one of the tax types incorporated in the hotel tax as stipulated in Law no. 28/2009 concerning Regional Taxes and Regional Levies on the provisions of which the hotel reads is the facility of providing lodging services, lodging including other related services with fee, which includes as well as motels, guesthouses, tourism huts, pensions, lodging houses and the like and boarding houses with more than 10 rooms. The purpose of this study is to determine the potential and effectiveness of local taxes on boarding houses in Kotamobagu City. The method used in this research method is qualitative. Tax receipts earned from 5 months will potentially increase PAD. As well as tax collection of boarding houses in Kotamobagu City experienced an effective increase in the first 5 months. The researcher concludes that the boarding house tax has big enough potency to be developed by Kotamobagu City Government where the Revenue Service, Finance and Regional Asset itself, with taxable boarding house can increase PAD Kotamobagu City.Keywords: PAD, Rumah Kos